2016
DOI: 10.1093/ejcts/ezw050
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized fresh homografts for pulmonary valve replacement: a decade of clinical experience

Abstract: OBJECTIVESDecellularized homografts have shown auspicious early results when used for pulmonary valve replacement (PVR) in congenital heart disease. The first clinical application in children was performed in 2002, initially using pre-seeding with endogenous progenitor cells. Since 2005, only non-seeded, fresh decellularized allografts have been implanted after spontaneous recellularization was observed by several groups.METHODSA matched comparison of decellularized fresh pulmonary homografts (DPHs) implanted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(108 citation statements)
references
References 25 publications
2
101
2
3
Order By: Relevance
“…It should not, if possible, trigger any thrombogenic effects. The graft must integrate into the host tissue and have the ability to grow, when used in children [69][70][71]. Furthermore, an easy manufacturing process, the shelf life of the vascular prostheses and readily available supply for an acute emergency, all play very important roles.…”
Section: The Ideal Vascular Prosthesismentioning
confidence: 99%
“…It should not, if possible, trigger any thrombogenic effects. The graft must integrate into the host tissue and have the ability to grow, when used in children [69][70][71]. Furthermore, an easy manufacturing process, the shelf life of the vascular prostheses and readily available supply for an acute emergency, all play very important roles.…”
Section: The Ideal Vascular Prosthesismentioning
confidence: 99%
“…Sarikouch et al reported good clinical results for more than 10 years with a fresh decellularized heart valve. 10 According to that report, compared with other valves such as homografts or Contegra ® , which are commonly used in Europe and the USA for patients with CHD accompanied mainly with RVOT dysfunction, the recurrence avoidance rate is significantly lower with fresh decellularized heart valves. Moreover, in Japan, for patients with CHD who have RVOT dysfunction, reconstruction is performed during infancy using artificial materials such as a transannular patch if the annulus cannot be preserved.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they reported no evidence of significant early activation of the cellular immune response 7 with extracellular matrix formation, which provided superior performance and showed growth potential corresponding with the excellent mid-term results of these valves in clinical use. 10 In Japan, re-operations for relatively young CHD patients with valvular dysfunction are increasing yearly, and the medical need for decellularized heart valves is considered very high. Therefore, in 2013 we started a joint clinical study of the safety of decellularized heart valve implantations with the Hannover Medical School.…”
mentioning
confidence: 99%
“…In vitro cultured TEHVs based on decellularized human pulmonary valves seeded with endothelial cells have demonstrated excellent hemodynamic performance and good functionality in clinical trials up to 10 years [59]. Thanks to the good functionality and the lack of degeneration, calcification and immunoreactivity, the use of decellularized allografts for both pulmonary and aortic valves is promising, with minimal occurrence of re-operations and possibility for adaptive growth [62,63]. Unfortunately, the availability of allografts is limited by donor shortage, leaving unmet the need for off-the-shelf available regenerative heart valve replacements.…”
Section: Technical Challenges: Cell and Scaffold Optimizationmentioning
confidence: 99%